Healing and reconciliation in a dysfunctional relationship : towards inter-religious functional relationship in Northern Nigeria - Tuduks, Oholiabs D. (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch Univesity, 2019.